Formulation development of a food-graded curcumin-loaded medium chain triglycerides-encapsulated kappa carrageenan (CUR-MCT-KC) gel bead based oral delivery formulation - Tan, Kei Xian (2021)
In recent years, curcumin has been a major research endeavor in food and biopharmaceutical industries owing to its miscellaneous health benefits. There is an increasing amount of research ongoing in the development of an ideal curcumin delivery system to resolve its limitations and further enhance its solubility, bioavailability and bioactivity. The emergence of food-graded materials and natural polymers has elicited new research interests into enhanced pharmaceutical delivery due to their unique properties as delivery carriers. The current study is to develop a natural and food-graded drug carrier with food-derived MCT oil and a seaweed-extracted polymer called k-carrageenan for oral delivery of curcumin with improved solubility, high gastric resistance, and high encapsulation of curcumin. The application of k-carrageenan as a structuring agent that gelatinizes o/w emulsion is rarely reported and there is so far no MCT-KC system established for the delivery of hydrophobic/lipophilic molecules. This article reports the synthesis and a series of in vitro bio-physicochemical studies to examine the performance of CUR-MCT-KC as an oral delivery system. The solubility of CUR was increased significantly using MCT with a good encapsulation efficiency of 73.98 ± 1.57% and a loading capacity of 1.32 ± 0.03 mg CUR/mL MCT. CUR was successfully loaded in MCT-KC, which was confirmed using FTIR and SEM with good storage and thermal stability. Dissolution study indicated that the solubility of CUR was enhanced two-fold using heated MCT oil as compared to naked or unformulated CUR. In vitro release study revealed that encapsulated CUR was protected from premature burst under simulated gastric environment and released drastically in simulated intestinal condition. The CUR release was active at intestinal pH with the cumulative release of >90% CUR after 5 h incubation, which is the desired outcome for CUR absorption under human intestinal conditions. A similar release profile was also obtained when CUR was replaced with beta-carotene molecules. Hence, the reported findings demonstrate the potencies of MCT-KC as a promising delivery carrier for hydrophobic candidates such as CUR.